Green Finance and India’s Climate Commitments: Aligning Financial Systems with Sustainable Development Goals - V. Basil Hans; Manjula Mallya M; N. Subbukrishna Sastry (International Journal of Sustainability, 2026)
India’s commitment to addressing climate change, as reflected in its Nationally Determined Contributions (NDCs), net-zero ambitions, and alignment with the United Nations Sustainable Development Goals (SDGs), has placed green finance at the center of the country’s sustainable development agenda. Green finance involves directing capital and investment flows toward projects and initiatives that are environmentally sustainable. It supports efforts to reduce climate-related risks, enhance resilience to environmental changes, and promote economic development that is both inclusive and ecologically responsible. Despite policy initiatives such as green bonds, sustainable banking frameworks, and climate-focused public investments, certain significant gaps remain in aligning India’s financial system with long-term environmental sustainability objectives. This study seeks to analyze how green finance contributes to India’s climate-related commitments and to evaluate the degree of alignment among financial institutions, capital markets, and policy mechanisms with the objectives of the Sustainable Development Goals. The researchers seek to analyze existing green finance instruments, evaluate regulatory and institutional mechanisms, and identify structural and operational challenges that limit effective implementation. The contribution of green finance to India’s climate commitments and to examine how effectively financial institutions, capital markets, and policy frameworks are aligned with the goals of sustainable development. The study adopts an analytical and descriptive research approach, supported by secondary data from government reports, regulatory publications, international climate finance databases, and peer-reviewed literature. The findings are expected to highlight the need for stronger policy coherence, improved disclosure standards, enhanced risk assessment frameworks, and greater private sector participation to scale up green investments. The researchers through their research contribute to the growing discourse on sustainable finance by offering policy-relevant insights for strengthening India’s financial architecture in line with its climate goals and SDG commitments.
Keywords: Environmental sustainability; climate change mitigation; climate policy; green bonds; green finance; sustainable development goals (SDGs); sustainable financial systems